EXPLORING THE IMPACT OF WORK-LIFE BALANCE, SELF-EFFICACY, AND EMPLOYEE ENGAGEMENT ON PERFORMANCE AT THE DINAS LINGKUNGAN HIDUP DAN KEHUTANAN PROVINSI KALIMANTAN BARAT - Hermanto, Jimmy Simanjaya; Lianto (Department of Management - Institut Shanti Bhuana, 2024)
This study aims to determine whether there is an influence of the variables Work-Life Balance, Self-Efficacy, and Employee Engagement on Employee Performance at the Dinas Lingkungan Hidup dan Kehutanan Provinsi Kalimantan Barat (Department of Environment and Forestry of West Kalimantan Province). This research uses questionnaire data collection techniques with a total of 90 office employees as respondents from the Dinas Lingkungan Hidup dan Kehutanan Provinsi Kalimantan Barat. The results show that the variables Work-Life Balance and Self-Efficacy have a positive and significant impact on Employee Performance, while the Employee Engagement does not significantly affect the improvement of Employee Performance. Therefore, it can be concluded that the Dinas Lingkungan Hidup dan Kehutanan Provinsi Kalimantan Barat shoud make Work-Life Balance and Self-Efficacy the main strengths in maintaining Employee Performance to provide a significant impact on the progress and service of the institution to the community.